Starch Sulfonation and Substitution with Amoxilline and Folic acid (Journal of the College of Basic Education, 2022)
Starch was sulfonated and substituted by Amoxilline and folic acid as natural drug polymer . Starch derivatives were characterized using FT.IR and UV spectroscopies. The synthesis and behavior of bioactive polymeric systems have attracted great interest in this work because the drug is lined to the polymer back – bone via a degradable chemical bond and it is slowly released under appropriate condition. The intrinsic viscosities were calculated using Ostwald viscometer at 30ºC. The controlled drug release was studies in different pH values. Thermal analysis was recorded and physical properties were measured.